Optimizing Motion Estimation for H.264 Encoding - Ludwich, Mateus Krepsky; Fröhlich, Antônio Augusto (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
Around 90% of the total encoding time of raw video into H.264 is spent in block-matching, a stage of Motion Estimation. In this paper we combine two block-matching optimizations that yield significant performance improvements on Motion Estimation: 4:1 subsampling by macroblock and truncation of the two less significant bits per sample. When applied to the JM Reference Encoder, our strategy showed an average speedup of 2.64 times in total encoding time with a small loss of quality (less than 0.5 dB).